2022
DOI: 10.1177/10711007221099197
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Closed Suction Drainage and No Drainage Following Total Ankle Arthroplasty

Abstract: Background: The purpose of this study is to determine whether the use of closed suction drains after total ankle arthroplasty (TAA) is associated with lower wound complications in the first postoperative year as compared to no drain usage. Methods: A total of 324 TAA were reviewed and included for analysis. One hundred forty-four did not have a postoperative drain placed, whereas 180 did have a postoperative drain. Demographic data, including age, sex, tobacco or alcohol use, and various medical comorbidities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…5 Although not a direct outcome of interest in our study, a recent assessment of 180 TAAs found that drains were associated with increased complications during the first 2 weeks postoperatively. 16 If present in our large-scale study, however, this outcome would likely be present in our outcomes through increased costs, length of stay, and readmission. There are several limitations to our study that should be recognized.…”
Section: Discussionmentioning
confidence: 87%
“…5 Although not a direct outcome of interest in our study, a recent assessment of 180 TAAs found that drains were associated with increased complications during the first 2 weeks postoperatively. 16 If present in our large-scale study, however, this outcome would likely be present in our outcomes through increased costs, length of stay, and readmission. There are several limitations to our study that should be recognized.…”
Section: Discussionmentioning
confidence: 87%